PEMANFAATAN AMONIASI UREA KULIT DAGING BUAH KOPI PADA PAKAN DOMBA TERHADAP KARKAS DOMBA JANTAN LEPAS SAPIH - Amelia Noveiza (Universitas Sumatera Utara, 2012)
ABSTRACT AMELIA NOVAIZA: Utilization of coffee flesh pod urea amoniased in sheep ration in Concentrate on Carcas of weaned sheep. Under the guidance of ARMYN HAKIM DAULAY as chairman and ISKANDAR SEMBIRING as commission member. The purpose of this research for see potential about the utilization of diamonized coffee flesh pod in sheep Concentrate on Carcas of weaned sheep. The research was done in Laboratory of Animal Biology Department of Animal science, Faculty of Agriculture, University of North Sumatera for 3 months from 20 August 2010 to 11 November 2010. The research methodology used 20 male sheeps with average inisial body weight 13.80 ± 1, 27 kg and using completely randomized design (CRD)method which consist of 4 treatments and 5 replication. The level of the concentrate which was given to diamonized coffee flesh pod is P0 (the concentrate given on non-diamonized coffee flesh pod is 30%), P1 (concentrate with coffe thear pod urea amoniased 15%), P2 (concentrate with coffe thear pod urea amoniased 30%), P3 (concentrate with coffe thear pod urea amoniased 45%). The result this research such as : empty body weight (kg/tail) data P0 = 12.74, P1 = 13:16, P2 = 13.00, P3 = 12.99, percentage of carcass data P0 = 49.19, P1 = 54.26, P2 = 53.79, P3 = 47.92, subcutaneous fat percentage data P0 = 1.91, P1 = 2.03, P2 = 1.95, P3 = 1.51, heart fat percentage data = 4:55 P0, P1 = 4.72, P2 = 4.25, P3 = 4.38, kidney fat percentage data P0 = 3.79, P1 = 4.05, P2 = 3.96, P3 = 3.68, data pelvic fat percentage P0 = 3.47, P1 = 3.70, P2 = 3.49, P3 = 3.27 all of the treatment effect is not real. Keyword: sheep, coffee flesh pod, ammonization,empty body weight, carcass, subcutan fat, kidney fat, heart fat, pelvic fat.